Pengembangan Sistem Pengumpulan Data Imunisasi Terpadu Elektronik untuk Mendukung Evaluasi Program Imunisasi Di Dinas Kesehatan Kabupaten Brebes - Lina Khasanah; Aris Puji Widodo; Farid Agushybana (Jurnal Manajemen Kesehatan Indonesia, 2017)
Immunization program includes planning, implementation, monitoring and evaluation of immunization activities. Implementation of immunization program evaluation through recording and reporting of immunization activities. The current immunization data recording system has not been able to produce complete, relevant, timely, accessible and easily understood information and has not provided a presentation of information that is easily interpreted according to the needs of the management.Implementation of information technology in the management of health data requires attention and conceptual framework as a whole. This is also required in the evaluation process of the immunization program at Brebes District Health Office. The provision of information that is interpretative and timely is needed in line with technological developments.The development of this immunization information system uses the FAST (framework for the application of systems techniques) method that produces input, process and output components that can cover the needs of immunization program reporting and evaluation of immunization programs through mapping areas.